Psychology as a Science - Dilnoza, Sarsenbaeva; Inyat, Abdikarimov; Miyribek, Dawletbaev (European Journal of Life Safety and Stability (2660-9630), 2023)
Psychology is the science of the patterns of development and functioning of the psyche. The interaction of all living beings with the outside world is carried out through a special kind of mental processes and states. These special processes are inseparable from physiological processes, but are not reduced to them. For many centuries, these amazing and mysterious phenomena were designated by the general term "soul" and were considered the product of a higher essence - God. In the views of the ancients, the soul was interpreted animalistically, i.e. as a special incorporeal entity that inhabits the human body. But already Aristotle proposed an interpretation of the soul as a way of organizing a living body and its behavior, which served as a powerful stimulus for the development of scientific views in the field of the mental in the West.